1987
DOI: 10.1172/jci113045
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of insulin secretion reveals heterogeneity of pancreatic B cells in vivo.

Abstract: We examined the immunofluorescence and ultrastructural changes of insulin-producing B cells in the center and at the periphery of islets of Langerhans during in vivo stimulation by glucose and glibenclamide. A decreased insulin immunostaining was detected in islets from the splenic rat pancreas after 1. IntroductionStudies on the insulin-producing B cells of the islets of Langerhans are usually performed with the implicit assumption that these cells are all alike and secrete synchronously and homogeneously un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
121
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 31 publications
15
121
1
Order By: Relevance
“…As expected from previous rodent studies [26,30], homologous contacts between human beta cells potentiated insulin secretion. In addition, and for the first time, we showed that a single intercellular contact between an alpha cell and a beta cell was able to increase insulin secretion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected from previous rodent studies [26,30], homologous contacts between human beta cells potentiated insulin secretion. In addition, and for the first time, we showed that a single intercellular contact between an alpha cell and a beta cell was able to increase insulin secretion.…”
Section: Discussionsupporting
confidence: 87%
“…There is no evidence in our data that this pattern of secretion exists in whole islets. In rats, heterogeneous secretion of islet beta cells has been demonstrated in vivo by systemic perfusion of glucose and glibenclamide [30]. Of course, this kind of experiment is impossible in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The amounts of both NCAM and integrins have thus been shown to differ from one b-cell to the next (Bosco et al 2000, Bernard-Kargar et al 2001, and functional heterogeneity has been documented by several groups (Salomon & Meda 1986, Stefan et al 1987, Pralong et al 1990, Soria et al 1991, van Schravendijk et al 1992. In the present study, the strongest labeling of E-cadherin was observed in the more central part of islets, corresponding to b-cells that have the higher insulin secretion activity (Stefan et al 1987). To further investigate whether a correlation does exist between E-cadherin expression and insulin secretion, we sorted by FACS a poorly labeled and a highly labeled b-cell population.…”
Section: Discussionmentioning
confidence: 99%
“…digestion (9,10). They were cultured on epithelial cell matrix (Becton Dickinson) in the presence of RPMI 1640 media (Life Technologies, Rockville, MD) supplemented with 11 mM glucose at 37°C and 5% CO 2 for Ϸ14 days before being used in experiments.…”
Section: Methodsmentioning
confidence: 99%